Aplicação de geotecnologias no planejamento de unidade político-administrativa municipal - Decian, Inajara dos Anjos da Silva (2005)
The municipal planning depends on the monitoring, permanent modernization and efficient administration of information about the quality of the ambiance, what can be accomplished through Geographical Information Systems -GIS - appropriately structured and implemented. The municipal district request a study that comes to lift, to analyze and to predict possible problems could make a monitoring with the objective of to modernize information and to support physical-environmental planning, because it is of great importance in the measure in that detects the disordered use that it causes deterioration in the atmosphere, seeking to decrease the impact of the action human. This way, the present work proposes the use of the geotecnologias for the planning of the Municipal district of Nova Palma/RS, generating a geographical database, in the intention of obtaining a municipal thematic mapping, proposing new adapted forms of use and occupation, objectifying larger effectiveness and speed in the implementing of restoring actions and, consequently, the improvement in the life quality. The elaboration of the thematic maps was good to trace a diagnosis of the municipal district, facilitating the visualization of the areas affected by environmental conflicts and, more susceptible areas the erosion, due to its relief with accentuated declivous and, mainly, the action negative antrópica verified in the practice of the agriculture, where most of the municipal districts with high sustentabilidade, coming of the rural section, as it is the case of the municipal district of Nova Palma, they disrespect the maintainable practices, seeking the high productivity, the immediate profit and, not the environmental preservation.